Pemberdayaan Perempuan Pelaku Pernikahan Dini melalui Pelatihan Desain, Kewirausahaan dan Keuangan di Desa Sambik Bangkol - Gozin Najah Rusyada; I Nyoman Switrayana; Risyaf Kudus Pranasa; Logi Mulawarman; Ridha Nurul Hayati (Insan Kreasi Media, 2023)
The rate of early marriage in Indonesia is still high. In terms of region, West Nusa Tenggara is the province with the highest number of women who have entered into early marriage at 16.23%. Like adolescents who have the potential to marry early, the community, especially women who have already married early, also needs attention. This service activity aims to empower women who have entered into early marriage through Design, Entrepreneurship and Financial Training. This activity uses the Service-Learning method. This activity was carried out in three stages, namely preparation, implementation and evaluation. The results of this activity show that the training can (1) increase participants' knowledge about the stages of designing product promotion media using the Canva application on cell phones, (2) increase digital entrepreneurship knowledge including formulating creative business ideas and advertising online on buying and selling platforms and (3) increase participants' knowledge regarding business financial management.